Development of Learning Media for Figure Books of Unit Words Dòngliàngcí for Students - Indriyani, Dwi Mei; Anggraeni, Anggraeni; Prasetiani, Dyah; Pamuji, Dian Yuni (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2024)
This research was conducted based on the results of initial observations carried out by researchers to determine the level of students' knowledge regarding Mandarin language units, especially material regarding 动量词 (dòngliàngcí) or verb units. Based on the results of initial observations, researchers found that the majority of Chinese Language Education Program students class of 2022 still do not understand 动量词 (dòngliàngcí). This is proven by the questions that researchers have distributed to students of the class of 2022 of the Chinese Language Education Program. This question contains Mandarin language units. From this question, the results showed that as many as 60% of students from the class of 2022 answered incorrectly to the question regarding 动量词 (dòngliàngcí). Apart from that, researchers also found that the learning media used in the classroom were limited to textbooks and PowerPoint presentations, so it could be said that the teaching media used to learn Mandarin words was still very lacking. Based on these problems, researchers conducted research on the development of learning media for Figure books with the unit word 动量词 (dòngliàngcí). The objectives of the research are 1) Describe the results of the analysis of needs for developing learning media for Figure books with the unit word 动量词 (dòngliàngcí) for Chinese Language Education Program students, 2) Describe the results of the prototype learning media for Figure book learning media with the unit word 动量词 (dòngliàngcí) for study program students UNNES Mandarin language education, and 3) Describe the results of expert validation of the learning media for Figure books with the unit word 动量词 (dòngliàngcí) for Chinese Language Education Program students. This research uses the Research and Development (R&D) method with five stages, namely 1) Potential and problems, (2) Data collection, (3) Product design, (4) Design validation, and (5) Design revision. Based on the results of the analysis of interviews with UNNES Mandarin language education lecturers and the results of the questionnaire analysis of the needs of Chinese Language Education Program students class of 2022, they agree with the existence of Figure book learning media with the unit word 动量词 (dòngliàngcí). The validation results by material experts obtained an average score of 87.5 with the number 4 (range of scores 86-100) and fell into the very appropriate or very appropriate category. The validation results from media experts obtained an average score of 87.25 with the number 4 (range of scores 86-100) and fell into the very appropriate or very appropriate category.